Corporate social responsibility: the case of the telecommunications sector. Issue 5 (8th August 2016) - Sutherland, Ewan
Abstract : Purpose: The paper aims to examine the reporting of corporate social responsibility (CSR) in the telecommunications sector and to consider how the obligations and regulations imposed on operators affect what is considered as CSR compared to other sectors. Design/methodology/approach: The paper provides a review of the academic literature on CSR, relating this to developments in the regulatory state and the adoption by governments and intergovernmental bodies of CSR instruments. Also, the paper conducts an analysis of coltan, greenhouse gas emissions and privacy as short case studies where CSR issues and regulations meet. Findings: Many activities that in other sectors would be considered CSR are required by licence or legislation, together with much more detailed scrutiny and reporting. Originality/value: The paper provides a review of existing literature on CSR in telecommunications, related to theories about CSR and the regulatory state.